A prospective observational study of vitamin D3 level in reproductive age group women with uterine leiomyoma - Annesha Dutta; Murari Mohan Koley; Priti Gautam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Uterine leiomyomas are the commonest benign tumours of the uterus with the incidence between 5.4 to 77% in Indian women. Vitamin D deficiency is a proven risk factor in the pathogenesis of uterine fibroid in many studies conducted in different parts of the world but not many studies have been conducted on Indian women. Methods: A total of 200 women of age group 18 to 45 years attending District Hospital, Howrah, West Bengal, were included in the study. Out of which, 100 had leiomyoma and rest healthy women without leiomyoma serves as controls. Routine ultrasound examination and serum hormone analysis of Vitamin D3 were done. Serum FSH, LH were done on day 2 of menstruation. Statistical analysis of data was performed using SPSS Version 22 software. Results: The mean serum concentration of vitamin D3 was significantly lower in women with uterine fibroids compared to controls (12.66±5.42 versus 25.91±14.18, p<0.003). On further analysis, 68.4% of cases were found to be severely deficient (vitamin D3 <9 ng/ml) as compared to 27.12% of controls (p<0.0002). Besides that, only 3.67% of cases had sufficient vitamin D level as compared to 22.16% of controls (p<0.0002). The odds ratio (OR) of occurrence of fibroid with serum vitamin D3 level of <12 ng/dl compared to that level >12 ng/dl was 5.38 (95% CI- 2.12-9.45) (p<0.0001). Conclusions: Serum vitamin D3 level inversely correlated with the burden of leiomyoma and possibly its deficiency is a causative factor for the occurrence of uterine fibroid in the reproductive age group women.